Ubiquity and diversity of human-associated Demodex mites. - Megan S Thoemmes (Public Library of Science (PLoS), 2014)
Demodex mites are a group of hair follicle and sebaceous gland-dwelling species. The species of these mites found on humans are arguably the animals with which we have the most intimate interactions. Yet, their prevalence and diversity have been poorly explored. Here we use a new molecular method to assess the occurrence of Demodex mites on humans. In addition, we use the 18S rRNA gene (18S rDNA) to assess the genetic diversity and evolutionary history of Demodex lineages. Within our samples, 100% of people over 18 years of age appear to host at least one Demodex species, suggesting that Demodex mites may be universal associates of adult humans. A phylogenetic analysis of 18S rDNA reveals intraspecific structure within one of the two named human-associated Demodex species, D. brevis. The D. brevis clade is geographically structured, suggesting that new lineages are likely to be discovered as humans from additional geographic regions are sampled.